Acute Osteomyelitis in Torus of Systemically Compromised Patients: Case Series - Boza-Oreamuno, Yadira V. (2022)
The torus are benign bony prominences that generally do not require treatment, however, they can occasionally present osteomyelitis (OM). The objective of this article is to describe the timely management of torus osteomyelitis through a series of clinical cases. Three patients with OM are reported. Two cases of men aged 66 and 69, diabetics, as well as a 57-year-old woman with a history of basal cell carcinoma of the nose. All had torus ulcers associated with trauma and without resolution of the same. In the three cases, a biopsy was performed to confirm the diagnosis and they were treated with anti-inflammatory drugs and antibiotic therapy, achieving complete resolution. Uncontrolled diabetes mellitus and trauma can favor the development of OM in patients with bone exostoses, therefore, when there are signs of infection in these structures, it is imperative to suspect the condition and offer treatment.